DAMPAK KEBIJAKAN WTO DALAM PAKET BALI 2013 TERHADAP PERTANIAN DAN KETAHANAN PANGAN INDONESIA - Ana Maria Siringoringo; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Since the establishment of the WTO in 1995, one of the trade regulated by the WTO is the agricultural sector with the existence of an Agreement on Agriculture (AoA). However, as a result of this agricultural agreement developing countries as an agricultural country have instead become importing countries for agricultural products (food), especially Indonesia. So that agriculture was renegotiated during the Doha Round of 2001. The purpose of this study was to find out and analyze the implementation and challenges of the WTO policies that existed in the 2013 Bali Package on agriculture and food security in Indonesia. This Bali package contains three pillars, namely facilitation of trade, agriculture and development for less developed countries. The method used in this research is descriptive analysis research method. This method is considered necessary because this method aims to describe the facts relating to the problem under study, along with the data used in this study is in the form of secondary data, obtained from scientific books, articles, electronic data and information. The results of the study indicate that the WTO policy on the Bali Package still results in Indonesian food security towards food imports. Although it is permissible to add subsidies, it is limited to a period of 4 years. Therefore, it is feared that there will be more imports of food products in Indonesia, which will weaken domestic food products. Thus Indonesia's food security is still dependent on imports and food sovereignty cannot be achieved.